Analysis of Academic Integration Processes of Syrian Students at Harran University - Mahmut Kaya; Hatice Şahin (İnsan & Toplum)
One of the main problems of Syrian refugees who took refuge in Turkey is education. Education is an important factor in the migration process as a tool of integration with the host society, preventing the risk of lost generation, reducing marginalization and radicalization, as a source of economic and social capital and upward social mobility. The subject of this study is the academic integration processes of Syrian students studying at Harran University. The research was carried out with a mixed method in which quantitative and qualitative methods were used together. The study is based on the results of a questionnaire with 326 people and a focus group meeting with 12 people. The study was conducted between March and December 2020. In the research, the results of the survey were analyzed through descriptive statistics, focus group interview thematic content analysis. According to the research findings; due to problems arising from war, immigration and other conditions, economic problems, language, exclusion and discrimination to a certain extent, accommodation, transportation, limited club membership and low participation in off-campus socialization processes, future anxiety in terms of employment, low book reading rate, factors such as insufficient household conditions, cultural ghettoization came forward. On the other hand friendship relations between the Syrian and Turkish students is a positive outlook. Satisfaction with academic and administrative staff is at a certain level. Şanlıurfa turns into a center of attraction to a certain extent in terms of education. Studying at Harran University is a joy for more than half of Syrian students. The results of the research show that a certain level of integration has been reached, but there are still aspects that are lagging and need to be strengthened.